2022
DOI: 10.1111/jop.13326
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of HDAC6 overcomes cisplatin chemoresistance by targeting cancer stem cells in oral squamous cell carcinoma

Abstract: Background Chemoresistance is associated with recurrence and metastasis in oral squamous cell carcinoma (OSCC). The cancer stem cell (CSC) subpopulation is highly resistant to therapy, and they are regulated by epigenetic mechanisms. HDACs are histone deacetylase enzymes that epigenetically regulate gene expression. HDAC6 acts on several physiological processes, including oxidative stress, autophagy and DNA damage response, and its accumulation is associated with cancer. Here, we investigate the role of HDAC6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Due to the expanding evidence that miRNAs are associated with chemotherapy resistance, the overall goal of this project was to evaluate both oral cancer resistance and miRNA expression to determine whether significant relationships could be identified. The results of this study clearly demonstrated at least two oral cancer cell lines (SCC9 and SCC25) with significant resistance to all three main chemotherapies (Cisplatin, 5-FU and Taxol), confirming recent observations made in other studies of chemotherapy resistance [ 29 , 30 , 31 , 32 ]. These data contribute to a body of important research that seeks to identify model systems for evaluating the mechanisms responsible for chemotherapy resistance among oral cancers [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…Due to the expanding evidence that miRNAs are associated with chemotherapy resistance, the overall goal of this project was to evaluate both oral cancer resistance and miRNA expression to determine whether significant relationships could be identified. The results of this study clearly demonstrated at least two oral cancer cell lines (SCC9 and SCC25) with significant resistance to all three main chemotherapies (Cisplatin, 5-FU and Taxol), confirming recent observations made in other studies of chemotherapy resistance [ 29 , 30 , 31 , 32 ]. These data contribute to a body of important research that seeks to identify model systems for evaluating the mechanisms responsible for chemotherapy resistance among oral cancers [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…41 When using LPS to stimulate primary bovine mammary epithelial cells, HDAC6 overexpression significantly induced ROS generation. 42 These contrasting results may be because of the different cell types used in the experiments because, in cancer stem cells, the administration of TubA increases ROS accumulation, 43 consistent with our findings. In addition, ROS can be produced by the activation of NADPH (NOX2) or mitochondria.…”
Section: Hdac6 Inhibition Accelerates Macrophage Bacterial Clearance ...supporting
confidence: 82%
“…Furthermore, HDAC6 has been implicated in autophagy and served as a critical regulator of cytoprotective response, bridging the connection between autophagy and Mubiquitin-proteasome system, mediating regulation between endoplasmic reticulum (ER) stress, autophagy and conferring chemoresistance in HNSCC [74]. Elevated levels of HDAC6 contributed to chemotherapy resistance in OSCC, making it a potential target for overcoming chemoresistance and preventing recurrence [75]. HDAC6 accumulation in cisplatin-resistant OSCC cells inhibited cell apoptosis by reducing reactive oxygen species (ROS) levels, diminishing DNA damage and increasing recombinant peroxiredoxin 2 (PRDX2) expression [75].…”
Section: Class II Hdacsmentioning
confidence: 99%
“…Elevated levels of HDAC6 contributed to chemotherapy resistance in OSCC, making it a potential target for overcoming chemoresistance and preventing recurrence [75]. HDAC6 accumulation in cisplatin-resistant OSCC cells inhibited cell apoptosis by reducing reactive oxygen species (ROS) levels, diminishing DNA damage and increasing recombinant peroxiredoxin 2 (PRDX2) expression [75].…”
Section: Class II Hdacsmentioning
confidence: 99%